Rethinking peer support for diabetes in Vancouver's South‐Asian community: a feasibility study. Issue 8 (9th January 2015) - Tang, T. S.; Sohal, P. S.; Garg, A. K.
Abstract Aim To examine the feasibility and potential health impact of a diabetes self‐management education and support intervention involving peer support on glycaemic control and diabetes distress. Methods A total of 41 South‐Asian adults with Type 2 diabetes were recruited for a 24‐week diabetes self‐management education and support pilot intervention involving peer support. The intervention consisted of six weekly education sessions co‐facilitated by a certified diabetes educator and two peer leaders, followed by 18 weekly support sessions facilitated by two peer leaders. Education sessions were guided entirely by participants' self‐management questions and also emphasized goal setting and action planning. Support sessions were based on empowerment principles and participants discussed self‐management challenges, shared emotions, asked self‐management questions, problem‐solved in a group, set goals, and developed and evaluated action plans. Feasibility outcomes included recruitment and retention. Primary health‐related outcomes included HbA1c levels and diabetes distress (measured at baseline, 6 and 24 weeks). Programme satisfaction was also assessed. Results Pre‐established criteria for recruitment and retention were met. Paired t‐tests showed no changes in HbA1c and diabetes distress at 6 weeks. At 24 weeks, HbA1c levels deteriorated [54 mmol/mol (7.1%) vs 61 mmol/mol (7.7%)] while diabetes distress scores improved (2.0 vs 1.7). Conclusions Although feasible, findings suggest this peer‐support model may have a positive impact on diabetes distress, but not on HbA1c levels. Culturally responsive modifications (e.g. intervention location) to the pilot model are needed and could lead to more favourable health outcomes for this community. Such a re‐designed peer‐support model will require further investigation.